Identification of nicotinamide phosphoribosyltransferase (NAMPT) inhibitors with no evidence of CYP3A4 time-dependent inhibition and improved aqueous solubility. Issue 3 (1st February 2015) - Zak, Mark; Liederer, Bianca M.; Sampath, Deepak; Yuen, Po-wai; Bair, Kenneth W.; Baumeister, Timm; Buckmelter, Alexandre J.; Clodfelter, Karl H.; Cheng, Eric; Crocker, Lisa; Fu, Bang; Han, Bingsong; et al.
Graphical abstract